Konsekuensi Penerapan Konsep Komunikasi Dalam Pelaksanaan Bisnis - Kristin Hutabarat, Yohana; Sitorus P, Lampola; Simbolon, Desmon; Febryola Hutapea, Dhea; Teguh Zega, Sepman; Tambunan, Naomi; Sun Bower Silalahi, Jeges; Tobing, Cindy (LPPM Universitas HKBP Nommensen, 2025)
Business communication is a strategic process in conveying information, ideas, and ideas to achieve a common understanding and support the achievement of organizational goals. This research aims to analyze the concept, form, purpose, and type of business communication based on theoretical studies. The research method The research was conducted using a qualitative approach involving a literature review of related sources.the results show that business communication includes verbal and nonverbal communication with an upward, down, lateral, and external communication flow. The effectiveness of business communication is influenced by perception, clarity of message, communicator credibility, control, and harmony of working relationships. Effective business communication contributes to increased productivity and organizational success.